2021
DOI: 10.1158/2326-6066.cir-20-1043
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of Gastrointestinal 5-HT Promotes Colitis-Associated Colorectal Cancer Progression via Enhancing NLRP3 Inflammasome Activation

Abstract: Chronic inflammation is a key driver for colitis-associated colorectal cancer. 5-hydroxytryptamine (5-HT), a neurotransmitter, has been reported to promote inflammation in the gastrointestinal tract. However, the mechanism behind this remains unclear. In this study, we found that 5-HT levels, as well as the expression of tryptophan hydroxylase 1 (TPH1), the 5-HT biosynthesis rate-limiting enzyme, were significantly upregulated in colorectal tumor tissues from patients with colorectal cancer, colorectal cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…In this study, we finally confirmed the oncogenetic role of TPH1 in OV cancer. TPH1 catalyzed the reaction of enhanced degradation of tryptophan to serotonin, and its oncogenetic has been discovered in breast cancer, bladder cell carcinoma, and colon cancer [31][32][33]. Similarly, we found that the knockdown of TPH1 inhibited OV cancer - clone formation and migration ability, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we finally confirmed the oncogenetic role of TPH1 in OV cancer. TPH1 catalyzed the reaction of enhanced degradation of tryptophan to serotonin, and its oncogenetic has been discovered in breast cancer, bladder cell carcinoma, and colon cancer [31][32][33]. Similarly, we found that the knockdown of TPH1 inhibited OV cancer - clone formation and migration ability, which is consistent with previous findings.…”
Section: Discussionsupporting
confidence: 91%
“…The latter finding sheds light on the link between pyroptosis and IBD-related CRC development ( Tan et al, 2020 ). Further, the overproduction of 5-HT in the gastrointestinal tract promotes IBD-related CRC progression by enhancing NLRP3 inflammasome activation ( Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentration was quantified by BCA assay (P0010S, Beyotime, Shanghai, China). Western blots were performed as previously described [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%